Translating the contemporary: Vladimir Sorokin and translation as criticism - Cavaliere, Arlete (RUS (Sao Paulo), 2020)
This essay presents and discuss some theoretical propositions about the literary translation's art, with regard to the translation of the Russian contemporaneity and Vladímir Sorókin’s novel Day of the Oprítchnik (Den’oprítchnika)